2005
DOI: 10.1248/cpb.53.1062
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of 2-Aryl-2-fluoropropionic Acids as Possible Platforms for New Medicinal Agents

Abstract: We have been studying the design, synthesis, and biological evaluation of chiral fluorine-containing organic compounds as effective analogues of pharmaceutically important molecules. Introduction of fluorine into a prototype molecule results in minimal steric alterations, which can facilitate interactions of fluorinated biomolecules or medicinals with enzyme active sites, receptor recognition sites, transport mechanisms, and other biological systems.1) On the other hand, the presence of fluorine can alter the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Ibuprofen methylester 4 was synthesized as previously reported [29]. Compounds 1-3 were synthesized as outlined in Scheme 1.…”
Section: Chemistrymentioning
confidence: 99%
“…Ibuprofen methylester 4 was synthesized as previously reported [29]. Compounds 1-3 were synthesized as outlined in Scheme 1.…”
Section: Chemistrymentioning
confidence: 99%
“…There are several reports on synthesis of a-fluo-rinated NSAIDs [17][18][19][20][21][22] and their biological evaluation. 23 Most of the reported synthesis involves fluorination of esters or derivatives of NSAIDs, 17,[19][20][21][22] and intractable and/ or hazardous reagents, such as diethylaminosulfur trifluoride (DAST), 17,22 perchloryl fluoride (FClO 3 ), 19 and acetyl hypofluorite (AcOF), 21 were used as a fluorinating reagent. By using the present EC of a,a-difluoroethylarenes, synthesis of a-fluorinated NSAIDs could be achieved under neutral and mild conditions without such reagents.…”
mentioning
confidence: 99%
“…The data of COX‐1/COX‐2 inhibition assay are mentioned in Table . SAR data (IC 50 values) acquired by the calculation of the in vitro potency of the heading compounds to inhibit the COX‐1 and COX‐2 isozymes displayed that the most peptides ( 1a–7b ) were acceptable inhibitors of the COX‐2 isozyme with IC 50 values in the 0.06–0.44 µM range, and COX‐2 selectivity indices in the 84.3–>500 range . Our results showed that the COX inhibition from the points of potency and selectivity was affected by the nature of amino acid substituents and SO 2 Me or N 3 pharmacophore at the para position of the end phenyl ring.…”
Section: Resultsmentioning
confidence: 76%
“…The ability of the synthesized compounds to inhibit ovine COX‐1 and COX‐2 (IC 50 value, μM) was determined using chemiluminescent enzyme assays kit (Cayman Chemical, Ann Arbor, MI, USA) according to the previously reported method .…”
Section: Methodsmentioning
confidence: 99%